Winter bird count from reports across the state contributed by Gladys Black, February 9, 1977 - Black, Gladyset al (1977)
Winter bird count from reports across the state contributed by Gladys Black. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed